ANALISA METODE MEDIAN PADA PENENTUAN TITIK TENGAH DI GOOGLE MAPS - Novianto, Kurnia Rizki; Sumarsono, Sumarsono; Indrianingsih, Yuliani (Compiler, 2014)
Information technology to used facilitate the lives of humans in performing activities have come to the stage of the hand grip. The intent of this grip is a form of computer that is small and can be hand held adult human hand, for example in the form of smartphones, laptops, and tablets. This equipment can help people to access the internet that provide maps and location services on earth . With the internet user will easily dig resources with ease. Thus with the internet it is essential for human life until the source of the future. Problems that arise in the world of internet or computer network often arise and prevent the problem. Limitations of resources based on google maps is very necessary for a person to get the intended location. This system will help a person in getting the distance of the intersection to a point latitude and longitude coordinates by calculating the midpoint of the user, and then calculate the distance between the midpoint of the location suggested by the system so that the user gets close location to conduct meetings. To specify the system location data using Google Place API to obtain complete data locations along the coordinates of latitude and longitude of a location .